The effects of kinesio tape on chronic low back pain among young adults in Ampang / Mohd Aimerul Mat Nuar - Mat Nuar, Mohd Aimerul (2015)
Chronic low back pain has been known as common injury among world citizen these days. Comprehensive knowledge regarding low back pain needed in term of understanding the component that caused lower back pain and how to manage it. Kinesio tape has been known as one of the elastic tape which help promoting healing in sport injury. The purpose of this study was to identify the effects of Kinesio tape on chronic low back pain among normal young adults in Ampang district. Twenty young male adults with chronic low back pain in Ampang district. The subjects were stratified purposively and subjects were randomly divided into two, experimental group and control group. The experimental group intervention was Kinesio tape over the lumbar spine for one week while the control group without a tape. The low back functional disability and low back mobility (Trunk flexion) were measured using the Oswestry Low Back Pain Disability Questionnaire and Modified-Modified Schober's Test. The following outcomes were measured at baseline, immediately after the first week, and four weeks later. The data were analyses using SPSS statistical software version 20. Repeated measures ANOYA was used to assess any differences between experimental and control group in 3 different times. The results from this study indicate that there were no significant differences between groups in both low back functional disability and low back mobility which p>0.05. In conclusion, Kinesio tape does not seem to be effective to improve lower back functional disability and low back mobility.